Ambient accountability: intelligence services in Europe and the decline of state secrecy. Issue 4 (4th July 2018) - Aldrich, Richard J.; Richterova, Daniela
Abstract: In the 1990s, judgments in the European Court of Human Rights concerning state surveillance forced many West European countries to introduce new parliamentary bodies and formal systems for accountability. Promising both greater transparency and lawful intelligence, these frameworks were then energetically rolled out to Central and Eastern Europe. Although officials boasted about their effectiveness, these formal accountability mechanisms have failed to identify serious abuses over the last decade. Moreover, the security regime in much of Central Europe still remains largely unreconstructed. The article argues that a robust culture of accountability cannot be conjured into existence merely by introducing new laws and regulations, or indeed by the increasing tide of media revelations about intelligence. However, it suggests that we are now seeing the rise of a more complex pattern of 'ambient accountability' which is at last challenging the secret state across Europe.